Adsorption performance of mesoporous silicas towards a cationic dye. Influence of mesostructure on adsorption capacity. Issue 4 (29th January 2019) - Meléndez‐Ortiz, Hector Iván; Puente‐Urbina, Bertha; Mercado‐Silva, Jesus Alfonso; García‐Uriostegui, Lorena
Abstract: The dye adsorption performance of four mesoporous silicas with different structure and textural properties, MCM‐41, MCM‐48, SBA‐15 and mesocellular silica foam (MCF), was studied and compared by using toluidine blue O (TBO) as dye model in aqueous solution. These materials were characterized by X‐ray diffraction (XRD), small‐angle X‐ray scattering, nitrogen adsorption‐desorption analyses, and transmission electron microscopy (TEM). The effect of some parameters such as adsorbent dosage, contact time, temperature, and pH on the TBO removal in aqueous solution was studied. Results showed that adsorption capacity raised when adsorbent dosage, contact time and pH solution were increased while an increase in temperature decreased the adsorption of TBO. Langmuir, Freundlich and Temkin isotherm models were employed to elucidate the adsorption mechanism while the adsorption rate data were analyzed according to the pseudo‐first and second‐order kinetic models. Results showed that adsorption of TBO onto MCM‐48, SBA‐15, and MCF fitted well the Freundlich isotherm model while the kinetic studies showed that adsorption process could be better described by the pseudo‐second‐order model for all mesoporous silicas. Finally, some solvents were evaluated to carried out dye desorption from the TBO‐loaded mesoporous silicas founding that acetic acid was the most efficient.